2018
DOI: 10.1007/s00056-018-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between oral health-related quality of life and orthodontic treatment need in children and adolescents—a prospective interdisciplinary multicentre cohort study

Abstract: Objective orthodontic treatment need significantly influences OHRQoL in children and adolescents. Further studies are required to investigate if OHRQoL may be improved by correcting misaligned teeth and jaws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 35 publications
2
19
0
9
Order By: Relevance
“…It was demonstrated that adolescents without concerning with teeth alignment presented 58% lower PR of being in the groups with high impact of OHRQoL than adolescent with such concern. This has been a common finding in other study of OHRQoL with adolescents 6 . Among the main implications of malocclusions on quality of life, discomfort in social interactions and problems with self-esteem have been highlighted 28 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…It was demonstrated that adolescents without concerning with teeth alignment presented 58% lower PR of being in the groups with high impact of OHRQoL than adolescent with such concern. This has been a common finding in other study of OHRQoL with adolescents 6 . Among the main implications of malocclusions on quality of life, discomfort in social interactions and problems with self-esteem have been highlighted 28 .…”
Section: Resultssupporting
confidence: 80%
“…The presence of caries lesions has been responsible for representing a negative experience regarding quality of life, and it is estimated that the more severe caries lesions, the higher will be the reflection on quality of life in children and adolescents 5 . Regarding malocclusion, it is currently demonstrated that the misaligned teeth and the need for orthodontic correction of the jaws are able to significantly influence quality of life 6 . It is still possible to indicate that this Oral Health-Related Quality of Life and Associated Factors in Institutionalized Adolescents relation turns more intense with increasing age, suggesting that in adolescents this association is more pronounced 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, addressing unmet dental needs is important in terms of public health. Unmet dental needs affect the dental health-associated quality of life in adolescents [74]. Improving dental healthcare services and meeting dental healthcare needs can therefore promote overall quality of life in adolescents; nevertheless, given the high expenditures required for dental healthcare, policy-makers are recommended to more effectively provide households with the financial support they need for this highly expensive care.…”
Section: Discussionmentioning
confidence: 99%
“…Both, economic and effectiveness aspects can influence the decision making, but mostly important, this decision have to consider the patient's needs, because dental restorative care and its long-term effects are directly related to children's OHRQoL (11,75,76,98,99). It is known that restorative treatment can impact on children's OHRQoL (27,77,100,101), although we can expect such type of effect for adhesive restorations, few studies have tested this hypothesis systematically (102).…”
Section: Chapter IIImentioning
confidence: 99%